De-Fueling Externalities: Causal Effects of Fuel Taxation and Mediating Mechanisms for Delivering Climate and Health Benefits - Pier Basaglia; Sophie M. Behr; Moritz A. Drupp (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper provides a comprehensive evaluation of the world's largest environmental tax reform. We compare carbon and air pollutant emissions of the German transport sector and synthetic counterfactuals following the 1999 eco-tax reform, and find average reductions in external damages of around 80 billion Euros. We further show that the eco-tax induced low-carbon innovation and document much stronger demand responses to eco-tax increases than to market price movements, primarily driven by increased tax salience in newspapers. Our results highlight the key roles of salience and fuel substitution in mediating the effectiveness of fuel taxes to deliver climate and health benefits.
Keywords: Q58; H23; I18; R48; 330; environmental policy; fuel tax; carbon tax; tax elasticity; salience; fuel substitution; innovation; climate; pollution; health